2016
DOI: 10.5194/wes-2016-45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric turbulence affects wind turbine nacelle transfer functions

Abstract: Abstract. Despite their potential as a valuable source of individual turbine power performance and turbine array energy production optimization information, nacelle-mounted anemometers have often been neglected because complex flows around the blades and nacelle interfere with their measurements. This work quantitatively explores the accuracy of and potential corrections to nacelle anemometer measurements to determine the degree to which they may be useful when corrected for these complex flows, particularly f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Thus, this study lays the groundwork for future investigations to compare the power output of the WFP scheme to the observed power production, which can be conducted with nacelle anemometer measurements (St. Martin et al 2017). Since mesoscale modelling is crucial in predicting power production in wind farms (Marquis et al 2011;Jiménez et al 2015;Wilczak et al 2015), comparisons of predicted and observed power output can help to identify areas for improvement in the WFP scheme in the WRF model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study lays the groundwork for future investigations to compare the power output of the WFP scheme to the observed power production, which can be conducted with nacelle anemometer measurements (St. Martin et al 2017). Since mesoscale modelling is crucial in predicting power production in wind farms (Marquis et al 2011;Jiménez et al 2015;Wilczak et al 2015), comparisons of predicted and observed power output can help to identify areas for improvement in the WFP scheme in the WRF model.…”
Section: Discussionmentioning
confidence: 99%
“…After phase averaging, all the velocity components exhibit signatures of blades passing with its intensity decreasing away from the rotor plane. Martin et al [39] reported different atmospheric conditions (e.g. stratification and turbulence intensity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The NTF is essentially a mapping from the wind speed measurement of nacelle‐top anemometer to the FSWS measured with met‐tower anemometry. Earlier work shows that the NTF‐based FSWS estimation achieves an R 2 (coefficient of determination) of 0.98 for a linear regression and 0.99 for a fifth‐order polynomial fitting . The annual energy production (AEP) calculated by the NTF‐based FSWS estimation yields an error less than 1% than that based on met‐tower measurement .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work shows that the NTF‐based FSWS estimation achieves an R 2 (coefficient of determination) of 0.98 for a linear regression and 0.99 for a fifth‐order polynomial fitting . The annual energy production (AEP) calculated by the NTF‐based FSWS estimation yields an error less than 1% than that based on met‐tower measurement . In particular, the use of spinner anemometer installed at the hub cover has shown more accurate and reliable FSWS estimation for upwind turbines …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation